Enhancing urban environmental quality through the development of green open spaces: An analysis of non-agricultural land use - Assyifa Fauzia (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Most areas in West Jakarta have fertile soil, making them suitable for a diverse range of urban vegetation. Urban vegetation communities offer numerous ecological, social, health, economic, and cultural benefits. The preservation of urban vegetation requires reliable data, one of which can be obtained through remote sensing using satellites. This data is crucial for informing the state and pressures on biodiversity in various urban areas. This study aims to analyze the distribution of vegetation on non-agricultural land to improve environmental quality and urban planning in West Jakarta. Methods: A qualitative approach was used, with secondary data and literature studies on several samples, assisted by Google Earth imagery for mapping the vegetation. Findings: The analysis reveals that non-agricultural lands are predominantly covered by alang-alang (Imperata cylindrica) grass, with these lands situated next to government and commercial centers. The findings suggest that there is potential for converting these areas into green open spaces (Ruang Terbuka Hijau/RTH), in accordance with the Regional Spatial Plan (Rencana Tata Ruang Wilayah/RTRW) for DKI Jakarta by 2030. Conclusion: The development of green open spaces from underutilized non-agricultural lands can contribute to improving environmental quality and enhancing the overall urban layout in West Jakarta. Additionally, the spatial structure of West Jakarta follows a sectoral model, where development focuses on specific land uses in distinct sectors. Novelty/Originality of this article: This article offers a novel perspective by integrating satellite-based remote sensing data with urban planning concepts, such as the sectoral model and green open space development.